Evaluation of risk factors for anal human papillomavirus infection in heterosexual women diagnosed with human papillomavirus associated cervical dysplasia: Risk factors for anal human papillomavirus infection - Özgen, Utku (Journal of Surgery and Medicine, 2023)
Background/Aim: Cervical dysplasia is a well-recognized precursor to cervical cancer, and human papillomavirus (HPV) infection is the primary causative agent in its development. The intricate relationship between cervical and anal HPV infections remains understudied. There have been no established risk factors determined for anal HPV infection in women without a history of anal intercourse. This study aims to address this critical knowledge gap by evaluating the risk factors for anal HPV infection in a homogeneous population of heterosexual women with HPV-associated cervical dysplasia. Methods: This retrospective cohort study was carried out in a single tertiary center and comprised women between the ages of 30 and 65. Women diagnosed with either low-grade squamous intraepithelial lesion (LSIL) or high-grade squamous intraepithelial lesion (HSIL) and without a history of anal intercourse were included in the analysis. Participants without a histological or colposcopic diagnosis were excluded from the analysis. Women with a history of prior cervical therapeutic intervention, previous cervical or genital dysplasia, known immunosuppressive disorders, current immunosuppressive medication use, a past cancer diagnosis, or a history of HPV vaccination were also excluded. Anal sampling was performed for HPV infection within the first year after the initial diagnosis of cervical dysplasia. Patient characteristics including smoking status were extracted from patient files. Results: Overall, 186 women who met the inclusion criteria were tested for active anal HPV infection of the anal canal. Active anal HPV infection was found in 96 (51.6%) of the patients. In women with active anal HPV infection, 31 (32.3%) were found to have only HPV 16/18 genotypes, and 22 had HPV16/18 along with other high-risk types. When risk factors were analyzed, only current smoking was found to be associated with anal HPV infection in this group of women. Overall, 40.6% of the women with active anal HPV infection were smokers; however, only 25.6% of the women without anal HPV infection were current smokers (P=0.029). Conclusion: Women had a high risk of active anal HPV infection during the diagnosis of cervical intraepithelial neoplasia. Current smoking was the only identifiable risk factor for anal HPV infection in women without anal intercourse history.